The Relationship Of Vegetable And Fruit Consumption With Nutritional Status Of Children School-Age (6-10 Years Old) At Ebf 28 De Agosto, Ebf 01 De Maio Palaban, Ebf St.Antonio Oe-Cusse, Ebf Nossa Senhora De Fatima Padiae Municipiu Regiao Administrativa Espesial Oe-Cusse Ambeno Timor Leste Year 2024 - Goreti Owa, Maria; Ningtyas, Rahaju; Palulun, Jeni; Paulo Oki, Joao; Bosco Dacosta, Joao; Trisnawati Setiawan, Christina (International Journal of Health and Pharmaceutical (IJHP), 2024)
This study aims to analyse the relationship between vegetable and fruit consumption and nutritional status among school-age children in Regiao Administrativa Espesial Oe-Cusse Ambeno Timor Leste, and to identify factors associated with children’s nutritional status. This study used a quantitative approach with a cross-sectional design. Data were collected through a questionnaire that measured the frequency of vegetable and fruit consumption, and measurement of nutritional status using anthropometric indicators. The study population was school-age children in Regiao Administrativa Especial Oe-Cusse Ambeno Timor Leste with the sampling technique used was simple random sampling. Fruit consumption patterns showed that 45.4% (79 respondents) of children rarely consumed fruit (<3 times per week). Most children were malnourished, with 69.5% (121 respondents) experiencing wasting. Another factor was preference for vegetables and fruits. These two factors showed a strong and significant association (r = 0.728 for vegetables, r = 0.725 for fruits, p = 0.000), indicating that children who had a high preference for vegetables and fruits were more likely to have better nutritional status. Child age was also found to have a significant but weak association (r = 0.278, p = 0.000) with nutritional status, suggesting that although influential, child age is not the main factor in determining nutritional status. Preference for vegetables and fruits had a significant relationship with children’s nutritional status. Age also has an effect, although it is weaker. No significant relationship was found between nutritional status and parental education, meal timing, and media exposure. The implication is that there is a need to increase vegetable and fruit consumption through nutrition education programmes in schools and communities, and the development of healthy eating habits.